Enhancing Crossdocking for a Green Supply Chain Based on IoT and AI - Raziq Ayoub; El Khaili Mohamed; Zamma Abdellah (E3S Web of Conferences)
In the realm of supply chain management, the integration of sustainable practices alongside competitive efficiency is increasingly crucial. This study explores the convergence of cross-docking methodologies with advanced technologies such as IoT and AI to enhance the sustainability of supply chains. Cross-docking, known for its direct transfer approach, minimizes storage duration and operational costs, potentially reducing environmental footprints associated with traditional logistics. Concurrently, IoT enables real-time monitoring of goods and environmental parameters, while AI-driven analytics optimize logistics operations with precision. This integrated approach not only enhances operational efficiency but also underscores the pivotal role of technological innovation in fostering sustainable supply chain practices. Insights from this study contribute to advancing sustainable logistics strategies tailored to contemporary environmental imperatives and industrial competitiveness.